Psalmy Salomona oraz ich echa w pismach Nowego Testamentu (cz. I) - Tronina, Antoni (The Biblical Annals, 2017)
After the introductory part discussing the historical background and the surroundings in which Solomon’s Psalms were composed, the article contains translations of the first eight psalms from Greek. In the footnotes there are references to the texts from the Old Testament which were used in Solomon’s Psalms and to the texts from the New Testament where literary similarities to the Psalms can be noticed.